Prevalence and risk factors for echinococcal infection in a rural area of northern Chile: a household-based cross-sectional study. - Gerardo Acosta-Jamett; Thomas Weitzel; Belgees Boufana; Claudia Adones; Andrea Bahamonde; Katia Abarca; Philip S Craig; Ingrid Reiter-Owona (Public Library of Science (PLoS), 2014)
Hydatidosis is a zoonotic disease of worldwide distribution caused by Echinococcus granulosus. Our study aimed to determine the prevalence of human and canine echinococcosis as well as the associated risk factors in a rural area of the Limarí province in northern Chile.A cross-sectional study was conducted between August and November 2009 using a stratified sampling design in each of the five districts of the province. In the selected villages, up to 10 households were sampled. Serum and fecal samples from an adult family member and a dog were collected from each participating household. Risk factors were assessed by standardized questionnaires. Seroprevalence was assessed using a multi-step approach: an ELISA for screening, IFA, IHA and western blot for confirmation of results, respectively. The prevalence of echinococcal infection in dogs was determined by coproantigen genus specific ELISA. Chi-square, Fisher tests and logistic regressions were used to assess risk factors for human seropositivity and dog copropositivity. A seroprevalence of 2.6% (10/403) and coproprevalence of 28% (26/93) was recorded for humans and dogs respectively. Contact with dogs and dog feces were risk factors for human seropositivity while dog copropositivity was associated with home slaughter of livestock (OR = 3.35; CI 90%: 1.16-6.85) and households de-worming dogs (OR = 2.82; CI 90%: 1.33-8.43).Echinococcal infection of humans and their dogs is common in Limarí province. Risk factors for human seropositivity were related to contact with domestic dogs and their feces, whereas those for dogs were home slaughter of livestock and the practice of de-worming dogs.